Pengaruh Aplikasi Beberapa Rhizobakteria terhadap Hasil dan Mutu Benih Padi Beras Merah (Oryza nivara L.) Lokal Jatiluwih - HANDAYANI, NI MADE YULI; PRADNYAWATHI, NI LUH MADE; MAYUN, IDA AYU; RAKA, I GUSTI NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
The Effect of the Application of Some Rhizobacteria on the Yield and Quality of Jatiluwih Local Red Rice ( Oryza nivara L.) Seeds This research aims to determine the effect of rhizobacteria on improving the yield and quality of local red rice seeds of Jatiluwih. The research used a Randomized Complate Block Design (RCBD) with one factor. The treatments tested were four types of rhizobacteria consisting of Serratia marcescens , Achromobacter spanius, Providencia vermicola and Pantoeae agglimerans , one treatment from a mixture of four rhizobacteria and one control (without rhizobacteria application). The results showed that the fourth mixture of rhizobacteria was able to improve the yield and quality of red rice seeds which was higher than the treatment using one rhizobacteria isolate. The average value of seed yield per hectare in the fourth rhizobacteria mixture treatment increased by 56.48%, in the treatment of one isolate it increased by 35.45%-36.67% compared to controls (average yield of 4.09 ton). The weight of 1000 rice seeds of red rice with a mixture of the four rhizobacteria isolates increased by 5.55% and the application of one rhizobacteria isolates increased by a range of 2.79%-3.30% compared to controls whose weight of 1000 seeds amounted to 27.59 g. The treatment application of the mixture of the four rhizobacteria isolates and the application of one rhizobacteria isolate were able to increase the vigor of storage capacity in the range of 3.86%-9.18% compared to controls whose storage vigor was 82.80%. It also has a significant effect on increasing vegetative and generative growth of red rice plants.